Omental apoplexy: Unravelling the mystery. Issue 3 (25th March 2020) - Moriarty, Heather K; Martin, Katherine; Koukounaras, Jim; Goh, Gerard S; Clements, Warren
Abstract: Introduction: To describe cases omental haemorrhage and to review the literature on this topic. Methods: We describe three cases of spontaneous omental haemorrhage and discuss various management strategies, in an attempt to provide direction for similar cases in the future. Results: A number of case reports of spontaneous or idiopathic omental haemorrhage exist in the literature. These cases are often attributed to an underlying vasculopathy, such as segmental arterial mediolysis (SAM). Appropriate resuscitation is paramount for best outcome. Severe bleeding may require surgery or transcatheter arterial embolisation, which is best performed early if required. Endovascular management using selective catheterisation of the bleeding vessel and embolisation is a minimally invasive alternative to emergent operative intervention. In the three cases we present, endovascular embolisation was performed in two patients, and surgical ligation in a third. Segmental arterial mediolysis is considered the likely aetiology in at least 2 of the 3 cases, based on imaging findings. No further episodes of haemorrhage occurred at follow‐up (ranging from 6 months to 2 years). Conclusions: Acute omental haemorrhage is a rare condition; however, it may be associated with significant morbidity and mortality. CT angiography is the imaging of choice. Management strategies include both endovascular and surgical intervention.